Economic Evaluation of Dupilumab Versus Endoscopic Sinus Surgery for the Treatment of Chronic Rhinosinusitis With Nasal Polyps. Issue 6 (5th January 2022) - Parasher, Arjun K.; Gliksman, Matt; Segarra, Daniel; Lin, Theodore; Rudmik, Luke; Quast, Troy
Abstract: Background: Dupilumab is a novel monoclonal antibody that recently received US Food and Drug Administration approval for the treatment of chronic rhinosinusitis with nasal polyps. Endoscopic sinus surgery (ESS) has been the mainstay of treatment for patients refractory to initial medical therapy. Data comparing the cost‐effectiveness of these treatments are scarce. The objective of this study is to compare the cost‐effectiveness of dupilumab and ESS treatment for patients with chronic rhinosinusitis with nasal polyps refractory to medical therapy. Methods: A cohort‐style Markov decision tree economic evaluation with 10‐year time horizon was performed. The two comparative treatment strategies were dupilumab therapy or ESS followed by postoperative maintenance therapy. Patients with response to treatment continued with either maintenance or dupilumab therapy; patients with no response underwent ESS. The primary outcome measure was incremental cost per quality‐adjusted life‐year calculated from Sino‐Nasal Outcome Test (SNOT‐22) scores. Sensitivity analyses were performed including discounting scenarios and a probabilistic sensitivity analysis. Results: The dupilumab strategy cost $195, 164 and produced 1.779 quality‐adjusted life‐years. The ESS strategy cost $20, 549 and produced 1.526 quality‐adjusted life‐years. This implies an incremental cost of $691, 691 for dupilumab for every 1‐unit increase in quality‐adjusted life‐year compared with ESS. Probability sensitivity analysis indicated that ESS was more cost‐effective than dupilumab in all iterations. Conclusions: While dupilumab and ESS may demonstrate similar clinical effectiveness, ESS remains the most cost‐effective treatment option and should remain the standard of care for patients with chronic rhinosinusitis with nasal polyps refractory to medical therapy.